Does CSR Disclosure Improve Firm’s Access To Finance And Reduce Firm Risk? - Erwin Saraswati; Anastasia Putri Lestari; Ananda Sagitaputri (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aims to find how CSR disclosure affects firm’s access to finance and firm risk, using empirical studies. The research uses secondary data from annual report and sustainability report listed in the manufacturing sector in Indonesia Stock Exchange (IDX). By using the purposive sampling method, a sample of 41 firms was obtained or 164 firm-years from 2015 to 2018. The study measures CSR disclosure by both quantity and quality to reflect the overall comprehensibility of the report. Data analysis is done with multiple linear regression method. The result shows that CSR quantity and quality increase a firm’s access to finance and reduce firm risk. Extensive and high-quality CSR reports are more favourable to investors, fund providers, and the society as a whole. It is because CSR improves a firm’s reputation and reduces agency problem. This supports legitimacy and agency theories. The limitation of this study is that it uses content analysis for CSR measures, so that there is an element of researcher's subjectivity. The results of these findings can be used as a consideration for companies to improve CSR disclosure and policy setting for regulators.